The Role of the school principal in the professional development of teachers from the school principals’ point of view in Bani Kenana District - Abu Alloush, Yusuf Mohammad (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the role of the school principal in the professional development of teachers from the point of view of school principals. The study also aimed to know the existence of differences related to statistical significance in the role of the school principal in the professional development of teachers in the school due to gender and educational stage variables. The study sample consisted of all principals of public schools in Bani Kenana District, and the sample was chosen in the (objective- purpose) method. The researcher used a questionnaire located on five levels according to Likert scale, which included (48) items distributed in (6) fields.An analytical descriptive approach was used to suit the study objectives. Statistical processing was carried out using the SPSS program, and the research reached the following results: that the role of the school principal in developing teachers professionally came at a low level, and that female principals give priority to developing teachers in the field of teaching methods and the use of educational methods, while school male principals give this field the last rank, the scientific field occupies the second rank for school female principals, while it takes the first rank for school male principals, and the researcher found through the results that there are no statistically significant differences in the role of the school principal in the professional development of teachers due to gender, or education stage.The researcher recommended paying attention to educating the principal of the school on the importance of his vital role in the professional development of teachers, And to have an active role in guiding and training teachers. That the principal of the school be of high scientific, professional, social and educational experience, and is aware of information, knowledge, skills, and methods that enable him to fulfill his role in the development of teachers. And that he has leadership qualities so that he can influence teachers positively, and provide them with services that help them perform their duties in a manner that is commensurate with the development of knowledge and technological progress.
Keywords: Role; School principal; Professional development for teachers; Bani Kenana District